2020
DOI: 10.20473/cdj.v9i2.2019.93-96
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogel Epigallocatechin-3-Gallate (EGCG) to the Number of Fibroblast Cell Proliferation in the Perforation of Wistar Rat Tooth Pulp

Abstract: Background: Pulpitis can occur because the deep cavity preparation and it causes increasing of NO levels. Perforated teeth require direct pulp capping (DPC) treatment. The current standard DPC material is calcium hydroxide. However, several studies have found weaknesses of calcium hydroxide that can affect the success of DPC treatment and new, more biocompatible materials are needed. Epigallocatechin-3-gallate (EGCG) in green tea has many benefits, including antioxidant, anticolagenase, anticancer, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
3
0
4
Order By: Relevance
“…Bahan tersebut juga memiliki beberapa kekurangan, seperti mudah larut, kemampuan adhesif terhadap dentin yang rendah, menyebabkan inflamasi, kemampuan sealing dalam jangka waktu lama yang kurang baik, serta pembentukan dentin reparatif dengan tunnel defect serta berporus. 5,6 Penelitian-penelitian terbaru mencoba untuk membuat suatu bahan yang bermanfaat dalam perawatan pulpa salah satunya dengan bahan-bahan seperti, nanohidroksiapatit, kolagen, dan Epigallocatechin-3-Gallate (EGCG). 4,5,7 Hidroksiapatit (Ca 10 (PO 4 ) 6 (OH) 2 ) adalah mineral anorganik dengan kandungan utama kalsium dan fosfat dengan rasio Ca/P sebesar 1,67 (stoikiometri).…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Bahan tersebut juga memiliki beberapa kekurangan, seperti mudah larut, kemampuan adhesif terhadap dentin yang rendah, menyebabkan inflamasi, kemampuan sealing dalam jangka waktu lama yang kurang baik, serta pembentukan dentin reparatif dengan tunnel defect serta berporus. 5,6 Penelitian-penelitian terbaru mencoba untuk membuat suatu bahan yang bermanfaat dalam perawatan pulpa salah satunya dengan bahan-bahan seperti, nanohidroksiapatit, kolagen, dan Epigallocatechin-3-Gallate (EGCG). 4,5,7 Hidroksiapatit (Ca 10 (PO 4 ) 6 (OH) 2 ) adalah mineral anorganik dengan kandungan utama kalsium dan fosfat dengan rasio Ca/P sebesar 1,67 (stoikiometri).…”
Section: Pendahuluanunclassified
“…5,6 Penelitian-penelitian terbaru mencoba untuk membuat suatu bahan yang bermanfaat dalam perawatan pulpa salah satunya dengan bahan-bahan seperti, nanohidroksiapatit, kolagen, dan Epigallocatechin-3-Gallate (EGCG). 4,5,7 Hidroksiapatit (Ca 10 (PO 4 ) 6 (OH) 2 ) adalah mineral anorganik dengan kandungan utama kalsium dan fosfat dengan rasio Ca/P sebesar 1,67 (stoikiometri). 8 Hidroksiapatit telah banyak digunakan dalam bidang ortopedi dan kedokteran gigi karena hidroksiapatit memiliki komposisi kimia yang sama dengan tulang dan gigi sehingga memiliki biokompatibilitas yang baik, osteokonduktif, non toksik, bioaktif, dan dapat didegradasi secara perlahan.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…in their study concluded that the different hydrogel EGCG concentration was effective in increasing the number of fibroblast cell proliferation when a concentration of 90 ppm was used. [ 10 ] Periodontitis is one of the most common infectious disorders. An in vitro study showed that the infected human PDL fibroblasts (hPDLFs) and human PDL stem cells (hPDLSCs) infected by a periodontal pathogen ( porphyromonas gingivalis ) EGCG showed anti-inflammatory effects on such fibroblast cells and found that EGCG could reduce inflammation in hPDLFs and hPDLSCs in response to P. gingivalis Lipopolysaccharide by Jung et al .…”
Section: Introductionmentioning
confidence: 99%